Pond water microbiome antibiotic resistance genes vary seasonally with environmental pH and tannins - Maya Vaccaro; Andrew M. Pilat; Logan Gusmano; Minh T. N. Pham; Daniel Barich; Audrey Gibson; Mwï Epalle; Dominick J. Frost; Elianajoy Volin; Zachary C. Slimak; Chelsea C. Menke; M. Siobhan Fennessy; et al. (Microbiology Spectrum)
ABSTRACT Microbial communities of small freshwater bodies interact dynamically with environmental factors in unknown ways. Longitudinal sampling of four ponds in Knox County, Ohio, revealed relationships among antibiotic resistance genes (ARGs) and environmental factors such as pH and tannin concentrations. For each site, microbial communities were collected by filtration, and metagenomes were analyzed by short-read sequencing. ARGs were quantified using the ShortBRED pipeline to detect and quantify hits to a marker set derived from the Comprehensive Antibiotic Resistance Database. The top 30 ARGs showed increased abundance at the end of the growing season. The top two ARGs with the largest marker hits encode components of a Stenotrophomonas drug efflux pump powered by proton-motive force (smeABC) and a mycobacterial global regulator that activates a drug pump and acid stress response (mtrA). The smeABC and mtrA prevalence showed a modest correlation with acidifying conditions (low pH and high tannic acids). Acidity amplifies the transmembrane pH difference component of the proton-motive force, thus increasing the cell’s energy available for pump function and ARG expression. Association with microbial taxa was tested by the Kraken2/Bracken predictor of taxa profiles. The ARG profiles showed the strongest acid dependence in ponds with a high proportion of Proteobacteria, whereas a pond with high Cyanobacteria showed the lowest ARG counts. Efflux pumps such as SmeABC and transcriptional activation by MtrA incur large energy expenditures whose function may be favored at low external pH, where the cell’s proton-motive force is maximal.IMPORTANCECompared to rivers and lakes, pond microbial ecosystems are understudied despite close contact with agriculture and recreation. Environmental microbes offer health benefits as well as hazards for human contact. Small water bodies may act as reservoirs for drug-resistant organisms and transfer of antibiotic resistance genes (ARGs). Yet, the public is rarely aware of the potential for exposure to ARG-carrying organisms in recreational water bodies. Little is known about the capacity of freshwater microbial communities to remediate drug pollution and which biochemical factors may select against antibiotic resistance genes. This study analyzes how aquatic ARG prevalence may depend on environmental factors such as pH and tannic acid levels.